Performance characteristics of long-track speed skaters: A literature review - Konings, M. J.; Elferink-Gemser, M. T.; Stoter, I. K.; van der Meer, D.; Otten, E.; Hettinga, F. J. (Sports Medicine, 2015)
Speed skating is an intriguing sport to study from different perspectives due to the peculiar way of motion and the multiple determinants for performance. This review aimed to identify what is known on (long-track) speed skating, and which individual characteristics determine speed skating performance. A total of 49 studies were included. Based on a multidimensional performance model, person-related performance characteristics were categorized in anthropometrical, technical, physiological, tactical, and psychological characteristics. Literature was found on anthropometry, technique, physiology, and tactics. However, psychological studies were clearly under-represented. In particular, the role of self-regulation might deserve more attention to further understand mechanisms relevant for optimal performance and for instance pacing. Another remarkable finding was that the technically/biomechanically favourable crouched skating technique (i.e. small knee and trunk angle) leads to a physiological disadvantage: a smaller knee angle may increase the deoxygenation of the working muscles. This is an important underlying aspect for the pacing tactics in speed skating. Elite speed skaters need to find the optimal balance between obtaining a fast start and preventing negative technical adaptations later on in the race by distributing their available energy over the race in an optimal way. More research is required to gain more insight into how this impacts on the processes of fatigue and coordination during speed skating races. This can lead to a better understanding on how elite speed skaters can maintain the optimal technical characteristics throughout the entire race, and how they can adapt their pacing to optimize all identified aspects that determine performance.